Antagonism of entomopathogenic fungi by Bacillus spp. Associated with the integument of cicadellids and delphacids - Toledo, Andrea Vanesa (2015)
Entomopathogenic fungi are potential tools to biocontrol cicadellids and delphacids, two groups of insects that cause extensive damage to agricultural crops. However, bacteria living on the host cuticle may inhibit fungal growth. In the present work, following the molecular characterization of 10 strains of Bacillus isolated from the integument of cicadellids and delphacids, we selected isolates of the fungi Beauveria bassiana and Metarhizium anisopliae that are resistant to the antimicrobials secreted by these bacterial strains. The antagonistic activity of the 10 bacterial isolates belonging to the genus Bacillus (i.e., B. amyloliquefaciens, B. pumilus, and B. subtilis) against 41 isolates of Bea. bassiana and 20 isolates of M. anisopliae was investigated in vitro on tryptic soy agar using the central disk test. With this approach, isolates of Bea. bassiana and M. anisopliae resistant to antagonistic bacteria were identified that can be further developed as biological control agents.